THE POSITION OF INDIRECT EVIDENCE AS VERIFICATION TOOLS IN THE CARTEL CASE - Veri Antoni (Fakultas Hukum Universitas Gadjah Mada, 2014)
Indirect (circumstantial) evidence, either economic evidence or communication evidence, has been used in cartel cases in many countries such as United States of America, Japan, Australia, Brazil, Malaysia, and others. According to Indonesia criminal procedure law, the position of indirect (circumstantial) evidence is categorized as an indication (clue evidence) whereas according to Indonesia civil procedure law, indirect (circumstantial) evidence is categorized as presumption. Considering the characteristics the antimonopoly law which aims to find material truth, the position of indirect evidence is more properly said to be an indication. Owing to its status as an indication, indirect evidence should be exhibited together with the other direct evidence. Indirect evidenceatau bukti tidak langsung, baik bukti ekonomi atau bukti komunikasi, telah digunakan dalam kasus-kasus kartel di banyak negara, seperti Amerika Serikat, Jepang, Australia, Brazil, Malaysia, dan lain-lain. Menurut hukum acara pidana Indonesia, posisi bukti tidak langsung dikategorikan sebagai indikasi (bukti petunjuk), padahal menurut hukum acara perdata Indonesia, bukti tidak langsung dikategorikan sebagai praduga. Mengingat karakteristik hukum anti-monopoli yang bertujuan untuk mencari kebenaran materiil, posisi bukti tidak langsung lebih tepat dikatakan indikasi. Karena statusnya sebagai indikasi, bukti tidak langsung harus dipamerkan bersama dengan bukti langsung lainnya.